The Effect of Social Media on Morality Among Youth in Kirigime Ward, Kabale Municipality, Kabale District. - Zakia, Lucky (Kabale University, 2023)
Social networking sites have become a very important aspect in young people's life. Internet use has grown considerably in the last decade and the majority of young adult uses the internet. The increased use of social media by teenagers across the world has several risks and consequences. They include privacy concerns such as sharing too much information, posting of false information about themselves or others, exposure to fraudsters, and addiction to the internet or social media use that might impact negatively on their social, psychological and emotional well-being. the purpose of this was to investigate the effect of social media on morality among youth in Kirigime Ward, Kabale Municipality, Kabale district.